An Empowerment Approach to Family Caregiver Involvement in Suicide Prevention: Implications for Practice. (July 2015) - Grant, Cynthia; Ballard, Elizabeth D.; Olson-Madden, Jennifer H.
Family members are often intimately involved in the suicidal crisis of a loved one but receive few resources and little support from the mental health community. As a result, these families can experience significant feelings of caregiver burden and powerlessness. This review outlines the experience of caring for a loved one at suicide risk, including potential barriers to involvement, risk and protective factors, and impact on the caregiver. One way to facilitate a caregiver's sense of self-efficacy when working with a suicidal client is to implement an empowerment-based family approach in treatment planning. In this piece, we propose an existing caregiver empowerment model, Creativity, Optimism, Planning and Expert information (COPE), that can be applied to any existing suicide prevention model to assist families in the treatment of clients who are at risk for suicide.